Achieving near-zero energy in hot climates: Retrofitting building envelopes for existing homes - Mohammed A Aloshan (Heliyon)
The retrofitting of existing residential buildings to achieve Near-Zero Energy Homes (NZEH) is crucial for global energy conservation and sustainability. As urbanisation and energy consumption increase, efficient energy use in residential buildings becomes increasingly important. This study is consistent with Saudi 2030 Vision Agenda, offering a model for other regions and emphasising the significance of sustainable development practices. By focusing on the residential sector, this study addresses a major area of energy consumption, providing practical solutions to reduce energy usage and promote environmental stewardship. Furthermore, the study presents a rigorous methodology for retrofitting existing residential buildings to achieve NZEH, centring on a residential villa in Riyadh, Saudi Arabia. DesignBuilder simulation tools were employed to systematically reduce energy consumption. Initially, a baseline scenario was constructed and verified against actual monthly electricity bills to ensure accuracy. The subsequent phase involved analysing 128 cases to determine the optimal configuration of the building's outer shell, considering key design variables like windows glazing, local shading devices and thermal insulation. The final phase integrated photovoltaic (PV) cells into the optimised model to generate sufficient energy, thereby attaining near-zero energy consumption annually. This methodology demonstrates the potential for substantial energy reductions in existing homes, advancing sustainable urban development and energy efficiency targets. The findings of this study reveal that the base-case scenario, with no retrofitting, had an annual energy consumption of 60,641 kWh. Optimising facade elements alone reduced energy consumption by 62 %, down to 37,801 kWh annually. The integrated PV systems further decreased net annual energy consumption to 9489 kWh, representing an 84 % reduction compared to the base case.